Is advancement of grapevine maturity explained by an increase in the rate of ripening or advancement of veraison?. (7th February 2021) - Cameron, W.; Petrie, P.R.; Barlow, E.W.R.; Patrick, C.J.; Howell, K.; Fuentes, S.
Abstract: Background and Aims: The major phenological events, such as harvest, are critical periods in the wine business calendar requiring much planning and organisation of resources, yet anticipation of the timing of these events is still imprecise. The aims of this study were to better understand why grape maturity (defined here as the day of the year the grapes reached 11.5 Bé) is advancing, and how different cultivars and regions are responding to the seasonal temperature conditions. Methods and Results: Trends in rate of ripening (Bé/day or Bé/°C day) and the day of year veraison (DOYV) were analysed at four Victorian vineyard regions and included 24 cultivars covering 20 years. There was a significant difference between cultivars in their rate of ripening with later ripening cultivars ripening more slowly (Bé/day). Higher yield slowed the rate of ripening (Bé/day), significantly at two vineyards. No significant temporal trends were observed for the rate of ripening nor for the interval between DOYV and day of year maturity (DOYM), as related to Vintage Year or Springtime Temperature (max), although these may become apparent with a longer series of data and resulting smaller confidence intervals. Different cultivars, however, had a significantly different rate of change for this interval over time, and higher yield was associated with a longer interval length. Day of year veraison advanced significantly as related to Springtime Temperature (max) at all vineyards, and at a significantly different rate for different cultivars at three of the four vineyards. There was a positive association between yield and DOYV. Conclusions: These results suggest that the observed advancement of grape maturity can be explained by the advancement of veraison, rather than an increase in the rate of ripening, for these cultivars in these regions. Significance of the Study: The study showed that there is existing cultivar diversity which, if better understood, could help better anticipate phenological timing, improve vineyard management and assist in adapting to climate change.